A Clinical Audit of the ReAktiv™ Posterior Dynamic Element (PDE) Orthosis on Ankle Trauma - Gardner, Sarah Louise (Auckland University of Technology, 2022)
Background: Injuries sustained during High Energy Trauma (HET) often require complex surgery and extensive rehabilitation and can result in long-term issues such as pain, loss of function and limitations in physical activity. The ReAktiv Posterior Dynamic Element™ orthosis is a custom-made Passive-Dynamic Ankle-Foot-Orthosis (PDAFO) that aims to alter impact and loading through the foot and ankle, reducing pain and allowing users to return to high levels of physical activity. The aim of this study was to conduct a case series on the clinical effectiveness of the ReAktiv PDE orthosis on pain and function for people that had sustained a HET injury to the lower limb. Methods: This case series retrospectively reviewed the results of three patients that had received the ReAktiv PDE Orthosis as a treatment intervention to alleviate pain and improve physical function following a HET injury to the ankle. To determine any changes in pain all participants completed the LEFS and completed a 2MWT prior to receiving the orthosis as part of the initial assessment. The PDQ and PSEQ were completed at the final fitting of the orthosis (2 weeks) and provided a baseline measure of how much the pain from their injury affected them on a day-to-day basis. A 6-week physiotherapy-led rehabilitation programme was established to help patients with gait retraining, functional movement patterns and returning to physical activity. Physical function was assessed using the 2MWT, FSST, TSA and SLB. The questionnaires (LEFS, PDQ, PSEQ) were re-recorded at the conclusion of the rehabilitation programme to determine any self-reported changes in pain since receiving the orthosis. All physical tests were re-recorded at the conclusion of the rehabilitation programme (6-weeks). Results: The ReAktiv PDE orthosis shows promise in improving self-reported pain levels in those who have sustained HET injuries to the ankle. Tracking of pain prior to receiving the orthosis, and again at the conclusion of the rehabilitation programme was recorded on 1 participant. The PDQ and PSEQ showed an improvement when using the orthosis and how much pain interfered with their life. The LEFS was recorded on two participants and showed improvement with both participants reporting a higher score at the conclusion of rehabilitation with the orthosis compared to baseline with no orthosis. Physical walking performance improved as indicated by the improvement seen in the 2MWT. Improvement in mobility and balance, measured through recording of the FSST, TSA and the SLB test at the commencement and conclusion of the rehabilitation programme was also seen. Conclusion: The ReAktiv PDE orthosis shows potential as a treatment option to improve pain levels and walking performance in those who have sustained a unilateral, HET injury to the lower limb. In addition to the application of the orthosis, the use of a 6-week physiotherapy-led rehabilitation programme, recorded further improvements in walking performance, physical mobility and balance. Further research conducted on a larger and more diverse cohort of ReAktiv PDE orthosis wearers, would help to determine the significance of the orthosis design on pain and physical performance, and the impact that the rehabilitation programme has on pain and physical function. Long-term follow up of users would also indicate whether the improvements that have been obtained during this short time frame are sustained in the long-term or whether participants experience regression due to further deterioration to their injured limb.